Capriccio Espagnol and other concert favorites: in full score - Rimsky Korsakov, Nicolai. 1844 - 1908 (Dover orchestral scores, 1998)
A towering figura among Russian composers of the late 19th century. Nicolay Rimsky-Korsakov (1844-1908) was one of music master archestrators. His artistry and innovations in controlling instrumental mass and color influenced an entire generation af composers-among them, his pupils Igor Stravinske and Ottorino Respighi, as well as Debussy, Ravel, Holst and other important figures of the early 20th century.